Influence of plastically anisotropic on formability in sheet metal using hole expansion test - Chaimongkon, Taratip; Ruangpradap, Montri; Bunyan, Tanongsak (RMUTSB ACADEMIC JOURNAL, 2025)
This research aimed to study the effect of anisotropic behavior of materials on the hole expansion ratio (HER) in cold rolled carbon steel sheets, grade SPCC, stainless steel, grade SUS304, and aluminum, grade AA1100 with thickness of 1.20mm. The hole expansion test is considered according to the ISO-16630 standard with both dimension cylindrical flat punch and conical punch at 60 degrees with a 50mm and diameter die of 52.70mm. Square sheets 150×150mm were pierced within 10mm at the center hole. After the test workpiece was formed until it cracked, the changed hole size of the test piece was measured to be the hole expansion ratio obtained from the experiment compared with the hole expansion ratio based on Hill’s 48 anisotropic yield criterion. The major and minor strains in the direction of the test piece were measured as diagonal and transverse rolling along the rolling direction, respectively, in order to determine the anisotropic hole expansion ratio and the anisotropic behavior of the material on the forming limit diagrams. As a result, hole expansion tests were conducted using a flat punch and a conical punch at 60 degrees and coupled anisotropic three-direction (i.e., 0o, 45o and 90o) relative to the rolling direction. The hole expansion ratios of SPCC material were 112.72, 100.56, 115.96, 150.24, 141.16 and 152.92%, respectively. The hole expansion ratios of SUS304 material were 30.04, 44.48, 32.36, 38.76, 51.48 and 39.12%, respectively. The hole expansion ratios of AA1100 material were 15.68, 20.78, 20.22, 20.65, 22.48 and 23.65%, respectively.